1997
DOI: 10.1104/pp.113.4.1309
|View full text |Cite
|
Sign up to set email alerts
|

On the Mechanism of Reinitiation of Endogenous Crassulacean Acid Metabolism Rhythm by Temperature Changes

Abstract: Under continuous light the endogenous Crassulacean acid metabolism (CAM) rhythm of Kalanchoe daigremontiana Hamet et Perrier de Ia Bâthie disappears at high (>29.0"C) or low (<8.0"C) temperatures. We investigated the reinitiation of rhythmicity when temperature was reduced from above the upper and increased from below the lower threshold leve1 via measurements of (a) short-term changes in carbon-isotope discrimination to illustrate shifts between C, and C, carboxylation in vivo, and (b) the malate sensitivity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
42
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 31 publications
3
42
1
Order By: Relevance
“…It has been suggested that the disruption of the circadian oscillations of CO 2 exchange in CAM plants by high temperature may be a consequence of increased efflux of malate from the vacuole to the cytosol, the site of PEPc activity (Wilkins, 1983;Grams et al, 1997). Figure 5 illustrates the physiological consequences of exposing either control leaves or leaves prevented from accumulating malate over the first half of the dark period (half N 2 ) to an 8°C increase in temperature in the middle of the night (from 2:30-3 am).…”
Section: Physiological Aspects Of Temperature Manipulationsmentioning
confidence: 99%
See 4 more Smart Citations
“…It has been suggested that the disruption of the circadian oscillations of CO 2 exchange in CAM plants by high temperature may be a consequence of increased efflux of malate from the vacuole to the cytosol, the site of PEPc activity (Wilkins, 1983;Grams et al, 1997). Figure 5 illustrates the physiological consequences of exposing either control leaves or leaves prevented from accumulating malate over the first half of the dark period (half N 2 ) to an 8°C increase in temperature in the middle of the night (from 2:30-3 am).…”
Section: Physiological Aspects Of Temperature Manipulationsmentioning
confidence: 99%
“…Thus, in order to completely inhibit PEP carboxylation at night, individual leaves of intact plants were enclosed in an atmosphere of N 2 overnight, as described by Borland and Griffiths (1997), thereby preventing access to external CO 2 and inhibiting the release of internal (respiratory) sources of CO 2 (full N 2 ). Some leaves were enclosed in an atmosphere of N 2 for the first half of the dark period (until 2 pm) and then exposed to ambient air for the remainder (half N 2 ).…”
Section: Manipulation Of Cammentioning
confidence: 99%
See 3 more Smart Citations